Outcomes of newly diagnosed acute myeloid leukemia with myelodysplasia related changes and elderly acute myeloid leukemia following decitabine therapy in combination with priming regimen. Issue 1 (1st January 2021) - Lai, Binbin; Mu, Qitian; Zhang, YanLi; Chen, Ying; Yan, Xiao; Ouyang, Guifang
ABSTRACT: Objectives: This study investigates efficacy of decitabine and priming regimen in treating newly diagnosed acute myeloid leukemia with myelodysplasia related changes (AML-MRC) and elderly AML. Methods: Totally 69 newly diagnosed AML-MRC and elderly AML treated with decitabine and priming regimen were enrolled. The effects of clinical characteristics, gene mutations and karyotype on remission rate and overall survival were investigated, as well as the effects of allogeneic hematopoietic stem cell transplantation on survival after remission. Results: There were 39 and 10 cases achieving complete remission (CR) and partial remission (PR), respectively, with CR rate of 56.5% and overall response (OR) rate of 71%. Moreover, 15 cases had no response (NR), with NR rate of 21.7%. There were 5 cases of death within 4 weeks after treatment, with early mortality rate of 7.2%. The factors of peripheral white blood cell count, bone marrow blast proportion, doubling of platelets after treatment, and co-mutation of three or more myeloid genes, significantly affected CR and OR rates, while age significantly affected OR rate. TP53 mutation and platelets not doubling after treatment were independent prognostic factors affecting overall survival. Conclusion: Combination of decitabine and priming regimen is effective in treating newly diagnosed AML-MRC and elderly AML.